PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI NEGERI SIPIL BIDANG PENGAWAS SEKOLAH PADA DINAS PENDIDIKAN PROVINSI RIAU - Maswir, Mulyadi (Eko dan Bisnis: Riau Economic and Business Review, 2021)
This research was conducted at the civil servant in the field of school superviors at the Riau Provincial Education Office. The population in this study amounted to 35 people. The sample in this research was taken based on the cencus method. The sample in this study amounted to 35 people. In analyzing the data obtained from this study the authors used descriptive analysis methods and quantitative analysis using SPSS version 23.0. From the results of research with descriptive analysis it is stated that the respondent's response to the work stress variable is agree and the performance variable of civil servants is agree. Based on the results of research with quantitative analysis, it is known that job stress has a positive and significant effect on the performance of civil servants as evidenced by the simple linear regression equation Y = 22.529 + 0.556 X and the t test results obtained by the t-value for the work stress variable of 5, 009(more greater than t table 2.03452.) with a significant level of 0.000 <0.05. From the determination test, it is known that (R2) is 0.432. Which means that the job stress variable has an effect of 43.2% on the performance of civil servants in the civil service police unit of Pekanbaru City, the remaining 56.8% is influenced by variable faktors that are not examined